MEDIA POLICY IN LOCAL TELEVISION MANAGEMENT IN CENTRAL JAVA (International Conference on Social and Islamic Studies, 2022)
Broadcast media governance carries out digitization, which refers to Article 72 of Law No. 11/2020 and Article 60A No. 32/2002. As many as 85% of developed countries in the world have migrated to digital broadcasting, but until now,  Indonesia is in the process of digitizing broadcasting. This study was conducted to describe the implications of media policies used in managing TVKU as one of the local television stations in Central Java related to the applicable law. The method used in this research is descriptive analysis with participant observation. The diffusion of innovation theory will be used to determine the process of adopting broadcasting digitization technology as a communication channel by TV Lolah Central Java, TVKU. The results showed that the government's mechanism in conducting socialization, models and roles in digitizing broadcasting caused local television stations to experience inequality in the implementation that occurred in the field. Various obstacles experienced by local television stations in digitizing broadcasting can affect the protection of their existence as broadcasters. The number of channels in digital broadcasting media compared to analogue broadcasting creates space as fierce competition for all television stations to become content providers , such as new digital television stations. As a result, local television stations unable to implement the broadcasting digitization process will experience broadcast closures. This research can be used as a reference for further research in media policy and local television station management.